Sociocognitive self-regulatory mechanisms governing judgments of the acceptability and likelihood of sport cheating - d'Arripe-Longueville, F.; Corrion, K.; Scoffier, S.; Roussel, P.; Chalabaev, A. (Journal of Sport & Exercise Psychology, 2010)
This study extends previous psychosocial literature (Bandura et al., 2001, 2003) by examining a structural model of the self-regulatory mechanisms governing the acceptability and likelihood of cheating in a sport context. Male and female adolescents (N = 804), aged 15-20 years, took part in this study. Negative affective self-regulatory efficacy influenced the acceptability and likelihood of cheating through the mediating role of moral disengagement, in females and males. Affective efficacy positively influenced prosocial behavior through moral disengagement or through resistive self-regulatory efficacy and social efficacy, in both groups. The direct effects of affective efficacy on beliefs about cheating were only evident in females. These results extend the findings of Bandura et al. (2001, 2003) to the sport context and suggest that affective and resistive self-regulatory efficacy operate in concert in governing adolescents` moral disengagement and transgressive behaviors in sport.